Alternative Management of River Watershed with Batulesa Method From Environmental Aspects - Sanam, Andriana E.; Nur, Muhammad SM; Messakh, Jakobis Johanis (Green Publisher Indonesia, 2022)
The research was conducted in the Meto Batulesa watershed, with a watershed area of 8,968 ha, located between two regencies, Kupang and Kupang city. The purpose of this research is to calculate the actual erosion rate and tolerable erosion, so that conservation alternatives can be found. Based on the map of land units, there are 19 land units that are then used for soil sampling, slope, observation of soil management and soil conservation. The sampling method used purposive sampling, the data taken to calculate erosion estimates using the Universal Soil Equation (USLE) method, while the erosion tolerance used the concept of equivalent depth and resource life based on (Hammer 1981) and (Arsyad 2010). The results of the study show that the highest actual erosion value of 225.68 tons/hectare/year and the lowest is 2.78 tons/hectare/year. The value of erosion tolerance among 19 land units, in which are 10 land units is above the erosion tolerance so that they require alternative management, while 9 of them are without conservation. Alternative management in the form of modifications to the values of C and P include 1. Terrace Gulud: Corn + Beans + Mulch of Plant Remnants, 2. Corn + Soybean with rotational cropping pattern + mulch of crop residues, 3. Bench terrace + corn cassava/soybean, 4. Secondary forest and 5. Primary forest.